2017
DOI: 10.1126/sciadv.1602794
|View full text |Cite
|
Sign up to set email alerts
|

Structural and biochemical differences between the Notch and the amyloid precursor protein transmembrane domains

Abstract: The Notch transmembrane domain exhibits significant structural differences from that of the amyloid precursor protein.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 95 publications
(171 reference statements)
1
45
0
Order By: Relevance
“…A recent structural study of γ-secretase cleavage 17 , reported that when native Notch is recognized by γ-secretase, the C-terminus of the TMD must be precisely positioned to form a hybrid β-sheet with the protease. Another structural study suggested that the RAM sequence behind the C-terminus of TMD could form a membrane docking domain 18 , which may help the positioning of TMD. Because the RAM sequence was not included in any published synNotch, we hypothesized that adding this natural motif might suppress LIA.…”
Section: Resultsmentioning
confidence: 99%
“…A recent structural study of γ-secretase cleavage 17 , reported that when native Notch is recognized by γ-secretase, the C-terminus of the TMD must be precisely positioned to form a hybrid β-sheet with the protease. Another structural study suggested that the RAM sequence behind the C-terminus of TMD could form a membrane docking domain 18 , which may help the positioning of TMD. Because the RAM sequence was not included in any published synNotch, we hypothesized that adding this natural motif might suppress LIA.…”
Section: Resultsmentioning
confidence: 99%
“…The FAD mutations consistently increase H-bond fluctuations in the region upstream to the ε-site while maintaining strong α-helicity near the cleavage sites. A stable helix near scissile bonds was found previously not only for the C99-TMD (Chen et al, 2014; Dominguez et al, 2016; Pester, Barrett, et al, 2013; Pester, Götz, et al, 2013; Takeshi Sato et al, 2009; Scharnagl et al, 2014), but also for Notch (Deatherage et al, 2017) and the SREBP-1 substrate of the intramembrane site-2 protease (Linser et al, 2015). The vicinity of the γ-site was shown, by solid-state NMR, to exist in a mixture of helical and non-helical conformations (Itkin et al, 2017; J.-X.…”
Section: Resultsmentioning
confidence: 67%
“…While the repertoire of conformational motions of the substrate TMDs is mainly determined by their α-helical fold architecture, there is reason to suspect that the relative importance of individual motions reflects differences in sequence and local fold. The TMD of NOTCH, another prominent substrate of GSEC (Beel & Sanders, 2008), appears to be a straight helix (Deatherage et al, 2017) missing the large-scale bending flexibility that characterizes the C99 TMD. As a result, the TMDs of NOTCH and C99 adapt differently to the hydrophobic thickness of the membrane environment (Deatherage et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the TMD of Notch1, as well as the TMD of the insulin receptor (IR), two other substrates of γ-secretase (9), have conformations very different from that of the C99 TMD as determined from solution-NMR of single-span TM helices in membrane mimics (100,101). In particular, Notch1 appears to be a straight helix, while the TMD helix of the might nevertheless provide the repertoire of functionally important motions necessary to adapt to interactions with the enzyme at different stages of the catalytic cycle.…”
Section: Discussionmentioning
confidence: 99%